Belowground competition among invading detritivores. Issue 1 (29th January 2016) - Chang, Chih‐Han; Szlavecz, Katalin; Filley, Timothy; Buyer, Jeffrey S.; Bernard, Michael J.; Pitz, Scott L.
Abstract: The factors regulating soil animal communities are poorly understood. Current theory favors niche complementarity and facilitation over competition as the primary forms of non‐trophic interspecific interaction in soil fauna; however, competition has frequently been suggested as an important community‐structuring factor in earthworms, ecosystem engineers that influence belowground processes. To date, direct evidence of competition in earthworms is lacking due to the difficulty inherent in identifying a limiting resource for saprophagous animals. In the present study, we offer the first direct evidence of interspecific competition for food in this dominant soil detritivore group by combining field observations with laboratory mesocosm experiments using 13 C and 15 N double‐enriched leaf litter to track consumption patterns. In our experiments, the Asian invasive species Amynthas hilgendorfi was a dominant competitor for leaf litter against two European species currently invading the temperate deciduous forests in North America. This competitive advantage may account for recent invasion success of A. hilgendorfi in forests with established populations of European species, and we hypothesize that specific phenological differences play an important role in determining the outcome of the belowground competition. In contrast, Eisenoides lonnbergi, a common native species in the Eastern United States, occupied a unique trophic position with limited interactions with other species, which may contribute to its persistence in habitats dominated by invasive species. Furthermore, our results supported neither the hypothesis that facilitation occurs between species of different functional groups nor the hypothesis that species in the same group exhibit functional equivalency in C and N translocation in the soil. We propose that species identity is a more powerful approach to understand earthworm invasion and its impacts on belowground processes.